Analisis Strategi Penghimpunan Dana ZIS Pada Program Peduli Pendidikan di DT Peduli Jambi - Ary Dean Amri; Dinda Angelina Ismanto; Annisa Annisa; Noviya Rita; Rizki Anggraini (JOURNAL OF SHARIA ECONOMICS, 2024)
The aim of this research is to determine the funding strategy implemented by ZIS for the education program at DT Peduli Jambi. The collection of ZIS funds in education programs can help achieve an education system in society, especially for underprivileged children. Of course, there are conditions that must be met to receive this education program. After that, DT Care Jambi will follow up for a survey. The research method used is a qualitative approach. DT Peduli Jambi aims to allocate ZIS funds effectively, such as distributing them to parties who need them and allocating them to existing programs at DT Peduli Jambi.